Slavemakers. - Wallace, Joseph (Ace Books, 2015)
Twenty years ago, venomous parasitic wasps known as thieves staged a massive, apocalyptic attack on another species - Homo sapiens - putting them on the brink of extinction. But some humans did survive. The colony called Refugia is home to a population of 281, including scientists, a pilot, and a tough young woman named Kait. In the African wilderness, there's Aisha Rose, nearly feral, born at the end of the old world. And in the ruins of New York City, there's a mysterious, powerful boy, a skilled hunter, isolated and living by his wits. As the survivors journey through the wastelands, they will find that they are not the only humans left on earth. Not by a long shot. But they may be the only ones left who are not under the thieves' control ...